Pengembangan Media E-Book Creator dalam Meningkatkan Keterampilan Membaca dan Menulis Permulaan Siswa - Dila Karinda; Intan Susetyo Kusumo Wardhani; Yovita Puspasari (STKIP AL HIKMAH SURABAYA, 2025)
Early reading and writing skills are initial abilities that must be mastered by lower-grade students. But in reality, second-grade elementary school students still have low initial reading and writing skills. This is evidenced by students who have not mastered punctuation, have unclear pronunciation, still repeating words in reading, and have not paid attention to neatness in writing. So a media is needed that can help solve these problems. This research develops E-Book Creator media to improve the initial reading and writing skills of elementary school grade II students. This research uses the ADDIE development model. Based on the results of validation, the E-Book Creator media is declared very valid for use. Based on the results of the differential test, there was an improvement in reading and writing skills starting with this media. Furthermore, based on the results of the N-Gain test, which is included in the effective category, so the use of E-Book Creator is effective in improving students' initial reading and writing skills.